Stem cell models of Angelman syndrome - Camões dos Santos, João; Appleton, Carolina; Cazaux Mateus, Francisca; Covas, Rita; Bekman, Evguenia Pavlovna; da Rocha, Simão Teixeira (Frontiers in Cell and Developmental Biology, 2023)
Angelman syndrome (AS) is an imprinted neurodevelopmental disorder that lacks a cure, characterized by developmental delay, intellectual impairment, seizures, ataxia and paroxysmal laughter. The condition arises due to the loss of the maternally inherited copy of the UBE3A gene in neurons. The paternally inherited UBE3A allele is unable to compensate because it is silenced by the expression of an antisense transcript (UBE3A-ATS) on the paternal chromosome. UBE3A, encoding enigmatic E3 ubiquitin ligase variants, regulates target proteins by either modifying their properties/functions or leading them to degradation through the proteasome. Over time, animal models, particularly the Ube3amat-/pat+ Knock-Out (KO) mice, have significantly contributed to our understanding of the molecular mechanisms underlying AS. However, a shift toward human pluripotent stem cell models (PSCs), such as human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), has gained momentum. These stem cell models accurately capture human genetic and cellular characteristics, offering an alternative or a complement to animal experimentation. Human stem cells possess the remarkable ability to recapitulate neurogenesis and generate "brain-in-a-dish" models, making them valuable tools for studying neurodevelopmental disorders like AS. In this review, we provide an overview of the current state-of-the-art in human stem cell models of AS and explore their potential to become the preclinical models of choice for drug screening and development, thus propelling AS therapeutic advancements and improving the lives of affected individuals.